Grooming Traffic to Maximize Throughput in SONET Rings - Colbourn, C J; Quattrocchi, G; Syrotiuk, V R (Journal of optical communications and networking, 2011)
Using a graph-theoretic formulation, a grooming in a SONET ring network may be interpreted as a decomposition of an undirected simple graph G=(V,E), where V corresponds to the n nodes in the ring, and each edge {i, j}ϵE represents the traffic requirements for the primitive ring {i, j}. In G = {G 1 ,...,G 8 }, the decomposition of G, each subgraph G i specifies a set of primitive rings assigned to the same wavelength. If the maximum size set is c then G is a c-grooming. In this paper, bounding the maximum through put tp̅ (c, n, ℓ) of a c-grooming G is addressed, subject to each node being equipped with a limited number ℓ of add-drop multiplexers (ADMs). Naturally, restricting the number of ADMs limits the achievable throughput. For all ℓ, precise determinations of maximum throughput for grooming ratios c=2, 3, and 4 are given. These underlie substantially improved bounds for larger grooming ratios.